Prognostic Relevance of Pretherapeutic Gamma-Glutamyltransferase in Patients with Primary Metastatic Breast Cancer - Staudigl, Christine; Concin, Nicole; Grimm, Christoph; Pfeiler, Georg; Nehoda, Regina; Singer, Christian F.; Polterauer, Stephan (PloS one, 2015)
Gamma-glutamyltransferase (GGT) is a known marker for apoptotic balance and cell detoxification. Recently, an association of baseline GGT levels and breast cancer incidence, tumor progression and chemotherapy resistance was shown. The purpose of this study was to evaluate the association of pre-therapeutic GGT levels, clinical-pathological parameters and survival in patients with primary metastatic breast cancer (PMBC). In this multicenter analysis, pre-therapeutic GGT levels and clinical-pathological parameters of 114 patients diagnosed with PMBC between 1996 and 2012 were evaluated. The association between GGT levels and clinical-pathological parameters were analysed. Patients were stratified into four GGT risk-groups (GGT < 18.00 U/L: normal low, 18.00 to 35.99 U/L: normal high, 36.00 to 71.99 U/L: elevated and ≥ 72.00 U/L: highly elevated) and survival analyses were performed. Patients in the high risk GGT group had a poorer overall survival, when compared to the low risk group with five-year overall survival rates of 39.5% and 53.7% (p = 0.04), respectively. Patients with larger breast tumors had a trend towards higher GGT levels (p = 0.053). Pre-therapeutic GGT levels were not associated with indicators of aggressive tumor biology such as HER2-status, triple negative histology, or poorly differentiated cancers. Pre-therapeutic GGT serum level might serve as a novel prognostic factor for overall-survival in patients with PMBC.